Em defesa do americanismo: O nascimento de uma nação de Griffith - Moço, Aline Campos Paiva (2010)
The object of this work is to analyze the concept of Americanism in the film The Birth of a Nation. The Birth of a Nation is one of the most controversial motion picture of the history of cinema and intent to show the story of the American Civil War and the Reconstruction of the South in the United States. The felling of nostalgia of his director, D. W. Griffith for the little white communities and its Protestantism and traditionalism approach the history of the film to the concept of Americanism before the First World War. The analyze of the film it s been made through the biography of his director, the period in which the film has been made called progressivism and the way how the historiography approach the same theme of the film